2017
DOI: 10.1504/ijex.2017.084523
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the tidal stream exergy in the ría de Vigo (NW Spain)

Abstract: Abstract:The exergy of the tidal currents in the ría de Vigo area (NW Spain) is quantified using the results of a 28-day long simulation of the tidal flows. The results show that the northernmost strait connecting the ría with the Atlantic Ocean is a promising site for tidal energy tapping, in contrast with the energetically weaker estuary. On the basis of the average power density (APD), a 7.5 km 2 region is identified in this strait as the most advantageous area to install tidal energy converters (TECs), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…As expected, the mid-ebb power for this spring tide is larger than the mid-flood power (0.45 kW/m 2 vs. 0.40 kW/m 2 ). In both cases, the power density values are considerably smaller than those found in other Galician rías: Vigo (7.5 and 5.6 kW/m 2 , for the mid-flood and mid-ebb, respectively [7]), Muros (5 -2 kW/m 2 [31]), or Ortigueira (8-6 kW/m 2 [6]).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…As expected, the mid-ebb power for this spring tide is larger than the mid-flood power (0.45 kW/m 2 vs. 0.40 kW/m 2 ). In both cases, the power density values are considerably smaller than those found in other Galician rías: Vigo (7.5 and 5.6 kW/m 2 , for the mid-flood and mid-ebb, respectively [7]), Muros (5 -2 kW/m 2 [31]), or Ortigueira (8-6 kW/m 2 [6]).…”
Section: Resultsmentioning
confidence: 61%
“…By using a long time series, it is expected to smooth out and quantify the variations in the tidal resource assessment that arise when shorter representative time windows (e.g., 14-day tidal cycles, or 28-day lunar months) are adopted. Previous studies comparing these shorter time periods [7,28] have shown that the potential tidal stream energy in an area can be under-or overestimated by as much as 16%, depending on whether the considered tidal cycle corresponded to a perigean or an apogean tide.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations